Revisão taxonômica do complexo Gonatodes concinnatus (Reptilia: Sphaerodactylidae) - STURARO, Marcelo José (Universidade Federal do Pará, 2013)
The Gonatodes concinnatus complex, as established here, consists of Gonatodes species characterized by a white suprahumeral spot with black margins; vermiculations on back; and transversely enlarged scales under the tail, showing the sequence 1’1’1”, and in some cases 1’1’2” (on the anterior portion). Two species are presently recognized in this Amazonian group, G. concinnatus and G. tapajonicus. New material found in eastern Amazonia (states of Pará and Amapá, Brazil) made it necessary to review species of this complex. We analyzed several populations within this complex, from Peru, Ecuador, Colômbia, and Brazil (but not from Venezuela), including those new records. Specimens were separated in groups defined on basis of color pattern. Stepwise discriminant function analyses were then performed to compare the external morphology (represented by measurements and scale counts, separately) in these groups. Results support recognition of four taxa, corresponding to G. concinnatus, from western Amazonia, in Ecuador and northeastern Peru; G. tapajonicus, from the Tapajós river basin, in Pará, Brazil; and two new species, one from eastern Amazonia, in the states of Pará and Amapá, Brazil, and another from cis-andean central Colombia. Diagnoses and descriptions of all species are presented.